How a teacher-librarian engages herself in collaboration activities in her school - Mohd Baharum, Azlina Nashriby (Persatuan Pustakawan Malaysia, 2008)
Teacher librarian plays a crucial role as a teacher and instructional partner in the teaching/learning activity development to support the teaching and learning innovation. Thus, there is a need to investigate the existence of such relationship in schools in Malaysia, as well as the level of collaboration between the teachers and the teacher-librarian. A single case study was carried out to look at a teacher-librarian involvement in collaborative activities in her school. Participant observation and interviews were carried out in order to obtain the finding. The finding showed a contrast result when two diffirent models were used to identify the extent of collaboration in the school.